EFFECT OF LECTURER SERVICE QUALITY AND INFRASTRUCTURE QUALITY ON STUDENT SATISFACTION - Sudirman Sudirman; Taryana Taryana; Yayuk Suprihartini; Ervina Maulida; Saut Maruli Tua Pandiangan (Journal of Innovation Research and Knowledge, 2023)
The purpose of this research is to analyze effect of lecturer service quality and infrastructure quality on student satisfaction. The type of research used is descriptive quantitative research. Population in this study are Private Higher Education Students in Medan City in 2023. However, because the official data for Private Higher Education Students in Medan City in 2022 is difficult to find, sample is taken randomly using snowball sampling technique. So sample in this study are 60 Private Higher Education Students in Medan City. The data analysis technique in this study used a partial (t) test. The results of the study show that lecturer service quality has a significant effect on student satisfaction. Infrastructure quality has a significant effect on student satisfaction.